US EXPERIENCE REGARDING PUBLIC-PRIVATE PARTNERSHIP IN THE SPHERE OF HIGHER EDUCATION AND THE POSSIBILITY OF ITS USE IN UKRAINE (Bulletin of criminological association of Ukraine, 2023)
It is emphasized that the system of higher education in the United States of America is determined by a high level of research activity and innovation. Universities and colleges actively fund important scientific projects, promoting scientific discoveries and technological developments. This, in turn, contributes to the development of modern solutions for various problems, and also stimulates interdisciplinary research. And, therefore, it is emphasized that interdisciplinarity is an important aspect of the education system, as it promotes the exchange of ideas between different branches of social life.It has been established that the United States of America has formed a fairly efficient and effective system of public-private partnership in the field of higher education, which is clearly evidenced by practice, as well as the fact that the higher education system in this country is one of the most prestigious in the world.It is argued that the most positive experience of the USA, which should be used by the domestic legislator in the framework of improving the relevant partnership, is the following: 1) active attraction of funds from the private sector, which are used to ensure the functioning of the institution of higher education, which allows to reduce the burden on the state budget; 2) US colleges and universities actively exchange technology and experience with private partners, which in turn makes it possible to develop not only science, but also a certain branch of production; 3) the parties to the partnership create opportunities for students and teachers to participate in advanced projects, thereby gaining the necessary practical experience; 4) technology transfer, which involves the transfer of technologies and knowledge, promoting innovation and economic growth; 5) private enterprises, especially multinational corporations, can contribute to the globalization of higher education by promoting international cooperation, exchange programs and joint research initiatives; 6) public-private partnership directly affects the flexibility of the education system, which adapts to the labor market, as well as socio-economic requirements.
Keywords: foreign experience; USA; legislation; higher education; public-private partnership